Pengembangan Media Pembelajaran Berbasis Fun thinkers book pada Materi Pancasila Kelas IV di UPTD SDN Kamal 2 - Nikita Tannia Dewi; Nilamsari Damayanti Fajrin (Universitas Maritim AMNI Semarang, 2023)
To increase students' enthusiasm for studying Pancasila, proper, effective, and interesting learning media is needed. However, the main obstacle is the lack of innovative and creative media which causes learning effectiveness to decrease and student interest to decrease. The purpose of this study was to develop a fun thinkers book-based learning media on Pancasila material for class IV at UPTD SD Negeri Kamal 2 that is valid, effective, and interesting. The research method used is research and development with a 4-D model which consists of 4 stages, namely define, design, develop, and dissemination. The subjects of this study were teachers and fourth grade students at UPTD SD Negeri Kamal 2. The results of the expert validation of the developed media obtained the results of the material expert validation I with a value of 96% and the material expert validation II with a percentage value of 98%. Followed by the results of the validation of the media expert I with a value of 97% and the validation of the media expert II with a percentage value of 95%, the expert validation gets an average percentage of 96.5% including the very valid category. This product is considered very interesting based on student and teacher response questionnaires with a percentage of 92.37%. The results showed that the fun thinkers book based learning media on Pancasila class IV material was very valid, effective, and interesting, so it was suitable for use in classroom learning.